2014
DOI: 10.5505/epilepsi.2014.30502
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic Seizures Related to Cerebral Venous Sinus Thrombosis: Clinicoradiological Findings and Cases of Delayed Diagnosis.

Abstract: Amaç: Çalışmamızda, epileptik nöbet ve status epileptikus gelişen serebral venöz sinus trombozlu hastaların klinik ve radyolojik özellikleri ile yanlış veya gecikmiş tanı nedenlerini sunmayı amaçladık. Gereç ve Yöntem:Çalışmaya Kasım 2012-Kasım 2013 tarihleri arasında yoğun bakım ünitesinde epileptik nöbet veya status epileptikus ile takip edilen ve serebral venöz tromboz tanısı alan dokuz hasta alındı. Tüm hastaların ayrıntılı nörolojik ve oftalmolojik muayeneleri ve elektroensefalografi, kranial tomografi, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Predictors of acute seizures included altered consciousness (GCS < 8), focal neurological deficit(s), hemorrhagic infarction, frontal lobe involvement, supratentorial lesions, SSS and CVs thrombosis [22]. Pregnancy and puerperium have been associated with a very high percentage of seizures in some studies but not others [14,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictors of acute seizures included altered consciousness (GCS < 8), focal neurological deficit(s), hemorrhagic infarction, frontal lobe involvement, supratentorial lesions, SSS and CVs thrombosis [22]. Pregnancy and puerperium have been associated with a very high percentage of seizures in some studies but not others [14,23].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy and puerperal CVST have been associated with a very high percentage of seizures in some studies [14,23]. Hüseyinoglu et al had found that supratentorial lesion, sagittal sinus thrombosis and puerperal CVST were associated with presenting seizures [22].…”
Section: Discussionmentioning
confidence: 99%